Deteksi Kematangan Buah Jambu Kristal Berdasarkan Fitur Warna Menggunakan Metode Transformasi Ruang Warna Hsv (Hue Saturation Value) Dan K-Nearest Neighbor - Adhi Wibowo; Diwahana Mutiara Candrasari Hermanto; Kusuma Indah Lestari; Hadion Wijoyo (Mahesa Research Institute, 2021)
Guava has properties that are easily damaged, improper handling of guava fruit can result in a decrease in quality and quality. In general, to measure maturity is still done manually, the weakness of this method is the level of accuracy that is not consistent and tends to experience errors. Utilization of images is very important to determine the maturity of guava fruit by utilizing digital images. With the existence of digital images, to determine the maturity of guava fruit based on its color, it can be done computing (technology-based), namely by applying image processing using the HSV (Hue, Saturation, Value) color space transformation method. The HSV (Hue, Saturation, Value) color model groups the intensity components of the carried color information (hue and saturation) in image colors. The results of the ripeness detection can be seen in each test with a percentage value of 91.67% for the ripe guava category, 90% for the raw guava fruit category. The percentage value for testing the overall data has a good percentage value which is influential in detecting the maturity of crystal guava, which is 95%. So it can be concluded that the detection of ripeness of crystal guava fruit can be done by applying the HSV color space transformation method.